Resolvemos problemas de reducción y ampliación de figuras geométricas en el plano cartesiano - Vargas Maguiña, Sonia Denis (2018)
Currently, the use of mathematics is very important and common in our daily and daily life, our purpose is to solve different mathematical problems._x000D_ The class "We solve problems of reduction and enlargement of geometric figures in the Cartesian plane" which was investigated for the students of the fifth grade of primary education section "A" of the Educational Institution Fe y Alegría N ° 19. This session aims to meet the needs of students in the different problems that may arise in their daily lives and presents an easy and interesting strategy for students to learn in mathematical problems._x000D_ The goal is for students to feel the pleasure of learning to solve problems very easily. To achieve this, consider an easy and interpretive strategy to solve problems suitable for fifth grade students of primary education with the appropriate means and materials of the new approach.